Inconsistencies in fertility preservation for young people with cancer in the UK. Issue 3 (20th September 2021) - Newton, Hannah L; Picton, Helen M; Friend, Amanda Jane; Hayden, Catherine M; Brougham, Mark; Cox, Rachel; Grandage, Victoria; Kwok-Williams, Michelle; Lane, Sheila; Mitchell, Rod Thomas; Skinner, Roderick; Wallace, W Hamish; et al.
Abstract : Objective: To assess the utilisation of and funding structure for fertility preservation for children diagnosed with cancer in the UK. Design: Survey of paediatric oncologists/haematologists. Questionnaires were sent electronically with reminder notifications to non-responders. Setting: UK Paediatric Oncology Principal Treatment Centres (PTCs). Participants: Paediatric oncologists/haematologists with an interest in the effects of treatment on fertility representing the 20 PTCs across the UK. Main outcome measures: Referral practices, sources and length of funding for storage of gametes or gonadal tissue for children diagnosed with cancer in the preceding 12 months. Results: Responses were received from 18 PTCs (90%) with responses to 98.3% of questions. All centres had referred patients for fertility preservation: ovarian tissue collection/storage 100% (n=18 centres), sperm banking 100% (n=17; one centre was excluded due to the age range of their patients), testicular tissue storage 83% (n=15), mature oocyte collection 35% (n=6; one centre was excluded due to the age range of their patients). All centres with knowledge of their funding source reported sperm cryopreservation was NHS funded. Only 60% (n=9) centres reported the same for mature oocyte storage. Of the centres aware of their funding source, half reported that ovarian and testicular tissue storage was funded by charitable sources; this increased in England compared with the rest of the UK. Conclusions: Inequality exists in provision of fertility preservation for children with cancer across the UK. There is lack of formalised government funding to support international guidelines, with resultant geographical variation in care. Centralised funding of fertility preservation for children and young adults is needed alongside establishment of a national advisory panel to support all PTCs. Abstract : This study highlights marked variation in provision and funding of fertility preservation services for children with cancer across the UK. Based on these findings, the authors argue that centralised NHS funding should be made available to ensure equitable provision of fertility preservation services and delivery of internationally acknowledged quality standards to all young people with cancer across the UK.